ANALISIS MARKOV CHAIN DALAM MEMPREDIKSI MARKET SHARE DAN EQUILIBRIUM PENGGUNA LAPTOP MAHASISWA AKTIF UNIVERSITAS UDAYANA - CHANDRI, PUTU REGINA PUTRI; SUPARTI, KADEK AYU ALIT; FRESILIA, NI MADE WAHYU; NOVRYANA, THIO; OCTAVANNY, MADE AYU DWI (E-Jurnal Matematika; Vol 13 No 1 (2024)DO - 10.24843/MTK.2024.v13.i01.p443, 2024)
The goal of this research is to assess the shift in laptop brands among currently enrolled students at Udayana University and predict the market share when the system reaches a stable state for each switch made by these students. The study employs the Markov Chain method, a component of Stochastic Processes. This method generates probabilistic information that aids in decision-making. In Markov Chain analysis, the equilibrium condition refers to a state in a specific period where the transition probability matrix stabilizes. Data on laptop brand switches were collected from users who have utilized more than one laptop brand. The study provides in-depth insights into the behavior of laptop users in the academic environment of Udayana University. The results of this research provide deep insights into the behavior of laptop users in the academic environment of Udayana University, laying the groundwork for a better understanding of market trends and user preferences.